1995
DOI: 10.1152/ajpendo.1995.268.6.e1077
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in the growth response of entire and gonadectomized rats to clenbuterol

Abstract: This study compared the anabolic effects of clenbuterol in male and female rats and determined the relative contribution of testicular and ovarian hormones to any observed gender difference. Seventy-two 12-wk-old rats were used in a 2 x 2 x 2 factorial design in which animals were either male or female, entire or gonadectomized at 3 wk of age, and fed either a control diet or a diet containing 4 mg clenbuterol/kg feed for 8 days. Compared with entire male rats, entire females gained 64% less weight, had lighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Castration also decreased the weight of the heart and kidney, and such changes have been reported previously (9,10,51). The castration-induced atrophy in these two tissues is not mediated by an altered rate of protein synthesis either under basal conditions or in response to leucine stimulation.…”
Section: Discussionsupporting
confidence: 86%
“…Castration also decreased the weight of the heart and kidney, and such changes have been reported previously (9,10,51). The castration-induced atrophy in these two tissues is not mediated by an altered rate of protein synthesis either under basal conditions or in response to leucine stimulation.…”
Section: Discussionsupporting
confidence: 86%
“…The current drug/body mass covariate accounted for the variance in relative b 2 agonist doses consumed by ALB-dosed subjects. Yet ALB-W still incurred the most favorable strength changes, in disagreement with prior results ( 32 ). Administration of the b 2 agonist clenbuterol led to greater muscle in both intact and castrated male rats vs. their female counterparts ( 32 ).…”
Section: Discussionmentioning
confidence: 58%
“…Yet ALB-W still incurred the most favorable strength changes, in disagreement with prior results ( 32 ). Administration of the b 2 agonist clenbuterol led to greater muscle in both intact and castrated male rats vs. their female counterparts ( 32 ). Genderrelated differences among current and prior results may be due to subject ages, the type of b 2 agonist given, and drug dosages.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Although males and females were weightmatched initially, it was not possible to provide weightmatched male and female 2K1C rats over the entire experimental period, since intact female 2K1C rats exhibit only a small weight gain, which is characteristic of growth in female rats in general [14][15][16][17][18]. However, there was no significant difference in BWs between the groups at the time of clipping when previous studies have shown that increased renin release can be detected as soon as 1-2 days after clipping [19].…”
Section: Discussionmentioning
confidence: 99%